Brown County Mornings - Moore, Gary, 1943- (Book collections on Project MUSE., 2013)
Rolling hills, rich forests, and beautiful vistas have made Brown County, Indiana, a favorite haunt of painters and ordinary tourists. In this gorgeous collection, a landscape photographer, reveals the spirit of the place in the morning hours as it awakens to the new day.